Respuesta :
For the given sequence, we can note that:
when we multiply a previous term by 1/4, we get the next term where:
2 * 1/4 = 1/2
1/2 * 1/4 = 1/8
1/8 * 1/4 = 1/32
Therefore, we can say that our sequencer here (r) is equal to 1/4
The general formula to represent this sequence is:
an = a1 * r^(n-1) where :
an represent the nth term that we want to find
a1 represents the first term in the sequence = 2
r is the sequencer = 1/4
n represents the order of the term in the sequence
Based on the above, the equation will be:
an = 2 * (1/4)^(n-1)
when we multiply a previous term by 1/4, we get the next term where:
2 * 1/4 = 1/2
1/2 * 1/4 = 1/8
1/8 * 1/4 = 1/32
Therefore, we can say that our sequencer here (r) is equal to 1/4
The general formula to represent this sequence is:
an = a1 * r^(n-1) where :
an represent the nth term that we want to find
a1 represents the first term in the sequence = 2
r is the sequencer = 1/4
n represents the order of the term in the sequence
Based on the above, the equation will be:
an = 2 * (1/4)^(n-1)